Peace versus Justice : Negotiating Forward- and Backward-Looking Outcomes. - Zartman, William I. (Rowman & Littlefield Publishers, 2005)
This book examines the costs and benefits of ending the fighting in a range of conflicts, and probes the reasons why negotiators provide, or fail to provide, resolutions that go beyond just 'stopping the shooting.' A wide range of case studies is marshaled to explore relevant peacemaking situations, from the end of the Thirty Years' War and the Napoleonic Wars, to more recent settlements of the late 20th and early 21st centuries-including large scale conflicts like the end of WWII and smaller scale, sometimes internal conflicts like those in Cyprus, Armenia and Azerbaijan, and Mozambique. Case.